Apakah Profitabilitas Memoderasi Pengaruh Penghindaran Pajak Terhadap Nilai Perusahaan? Bukti Empiris dari Indonesia - Rahman, Arief; Astuti, Ayu Tri (E-Jurnal Akuntansi, 2022)
The purpose of the study was to examine the effect of tax avoidance and audit quality on firm value with profitability as a moderating variable. Measurement of tax avoidance is carried out using the Effective Tax Rate (ETR). Meanwhile, audit quality uses a dummy indicator, namely the classification of the Big Four KAP auditors and KAP auditors Other than the Big Four and profitability is measured using Return on Assets (ROA). This study involved a sample of 54 companies that were registered on IDX in 2015-2019. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that tax avoidance had no effect on firm value, although audit quality had a positive effect on firm value. The moderating variable for profitability affects the relationship between tax avoidance and firm value, but the moderating variable for profitability does not affect the relationship between audit quality and firm value. Keywords: Tax Avoidance; Profitability; Firm Value; Audit Quality.